The evaluation of pharmacokinetic parameters of 4-(5-methyl-1,3,4-oxadiazole-2-yl)-benzenesulfonamide and its metabolites in rat plasma - Alexander L. Khokhlov; Ilya I. Yaichkov; Anton A. Shetnev; Mikhail K. Korsakov; Nikita N. Volkhin; Sergey S. Petukhov; Alena N. Tyushina; Olga E. Lasaryanz (Research Results in Pharmacology)
Introduction: 4-(5-methyl-1,3,4-oxadiazole-2-yl)-benzenesulfonamide (ODASA) is a new pharmacologically activecompound, which is capable of reducing intraocular pressure by inhibiting carbonic anhydrase II. It is necessary to calculate the pharmacokinetic parameters of this compound and its metabolites in blood plasma of laboratory animals during a preclinical study. Aim: Evaluation of pharmacokinetic parameters of ODASA and its metabolites in rat bloodplasma after instillation of ocular suspension and its intraperitoneal administration.